2021
DOI: 10.23986/afsci.110877
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality in growing-finishing pigs fed diets with plant-based protein sources alternative to genetically modified soybean meal

Abstract: The objective of this study was to evaluate carcass and meat quality in growing-finishing pigs fed diets with different vegetable protein sources. It was found that partial (50% in grower diets) and complete (100% in finisher diets) replacement of protein from genetically modified soybean meal (GM-SBM) with protein from 00-rapeseed meal (00-RSM), alone or in combination with protein from faba bean seeds (FB) cv. ‘Albus’, yellow lupine seeds (YL) cv. ‘Taper’ or corn DDGS, had no significant effect on carcass qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…However, the pH 45min , pH 24h , L*, a*, h*, cooking loss, drip loss, shear force, and marble score were not influenced by adding DDGS to the diets (p > 0.05). The physicochemical properties of meat affect the appearance, shelf life, and sensory quality and contribute to the assessment of the overall level of different meats [23]. In this study, we could not observe significant effects of DDGS on pH, drip loss, cooking loss, shear force, and marble score.…”
Section: Meat Quality Traitscontrasting
confidence: 62%
See 1 more Smart Citation
“…However, the pH 45min , pH 24h , L*, a*, h*, cooking loss, drip loss, shear force, and marble score were not influenced by adding DDGS to the diets (p > 0.05). The physicochemical properties of meat affect the appearance, shelf life, and sensory quality and contribute to the assessment of the overall level of different meats [23]. In this study, we could not observe significant effects of DDGS on pH, drip loss, cooking loss, shear force, and marble score.…”
Section: Meat Quality Traitscontrasting
confidence: 62%
“…Similar to our study, Lee et al [28] showed that the addition of 20% DDGS to the diet did not affect the chemical composition of the LT in finishing pigs. Smiecinska et al [23] also failed to observe the differences in the above chemical components after adding DDGS to the diet. This indicates that feeding DDGS does not significantly affect the chemical composition of the LT in finishing pigs.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Meat cubes weighing around 50 g were cut out from the muscles across the grain. The samples were heated in 0.6% NaCl solution (solution to sample ratio of 2:1 v / v ) at a temperature of 96 °C for 1 h. The sensory analysis was performed under standard conditions, immediately after heat treatment, by six trained panelists selected for their sensory sensitivity, on a five-point scale (1 points—lowest grade; 5 points–highest grade) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%